Manajemen Strategi Pelayanan Perizinan Usaha Pada Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kabupaten Karawang - Trianti, Salsa; Febriantin, Kariena (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the management of licensing service strategies at the Investment and One-Stop Integrated Service Office (DPMPTSP) of Karawang Regency. The background of this study is based on the many problems in business licensing services, such as complaints from investors and business actors regarding delays, document inconsistencies, and the suboptimal use of the Online Single Submission (OSS) system. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. Data analysis uses the Miles and Huberman interactive model. The theory used is the strategic management theory from Kooten (in Ulfa, 2018) with four main dimensions: organizational strategy, program strategy, resource support strategy, and supporting and inhibiting factors. The results of the study show that the DPMPTSP of Karawang Regency has made efforts to improve the quality of service by developing a licensing information system, providing assistance, and opening various public complaint channels. However, there are still obstacles such as low digital literacy of the community and technical constraints in the implementation of OSS. This study recommends the need to strengthen human resource capacity and cross-agency synergy to create effective, efficient, and responsive licensing services. Keywords: Strategic Management, Licensing Services, DPMPTSP, OSS, Karawang Regency